Characterization of amylopectin and soluble starch synthase activities in endosperm of different rice cultivars (Oryza sativa L.) - Mar, Nyo Nyo (2012)
Rice (Oryza sativa L.) is consumed by more than half of world’s population and is also the main staple food in Asian countries. Modernization of agricultural methods has to consider the expansion of rice production areas, crop yield and nutritional quality of the product. Starch in rice is made up of two types of glucose polymers, amylose and amylopectin. Amylopectin is a branched polymer which composed of α-1,4-linked glucose and α-1,6 linked branch points, whereas amylose has no branch points. Both amylose and amylopectin are major criteria in evaluating rice quality. It has been reported that the SSIIa enzyme in rice cultivars contributes to the eating and processing qualities of rice, since it influences structural differences in amylopectin. South East Asia especially Myanmar and Malaysia, the rice cultivars with superior traits have rare potential productivities since there is a lack of information on preferable breeding traits. The present study is focused on characterization of starch in different rice cultivars since it is a very important factor in determining rice grain quality. A total of sixteen Myanmar rice cultivars, three Malaysian lines and three control cultivars were used in this study. The use of fluorophore-assisted carbohydrate electrophoresis through capillary electrophoresis enabled the classification of the three different types of amylopectin. The six rice cultivars (Khun Ni Shay, Ta Soke Pwa, Thet Nu Saba Net Pyan, MR219, MR219-4 and MR219-9) were to have long (L-type) amylopectin as rich in intermediate chain length of amylopectin (52.5-55.3%), whereas Ka Gaw Saw, Nga Sein, Yoe Wa, Shwe War Tun Kauk Hnyin, Padan Nga Sein, and Ya Ta Pa Lay were observed to have intermediate (M-type) amylopectin as middle rich in intermediate chain length of amylopectin (48.3-49.9%), while Nga Pya Gyi, Na Pal, Shwe Li-2, Kauk Yar Gyi, Khao Pa Phone, Ye Baw Yoe Sein and Khao Nao were indicated to have short (S-type) amylopectin type as low in intermediate chain length of amylopectin (47.2-48.6%). The result of 1.7% KOH test further supported that the L-type and M-type rice cultivars were relatively resistant to alkali solution while the S-type was highly susceptible to alkali degradation. In the case of starch gelatinization characteristics, the M-type and L-type amylopectin generally showed light violet with iodine staining while S-type endosperm was dark violet. The results of differential scanning calorimeter (DSC) analysis showed that the classification of the amylopectin since gelatinization temperature (GT) affected the amylopectin chain length distribution. Low GT indicates a range of 67.2-69.6°C, intermediate GT indicates a range of 70.2-72.5°C while high GT is in the range of 73.6-78.4°C. Generally S-type amylopectin rice has low GT group while M-type and L-type amylopectin rice have intermediate to high GT. The different rice cultivars also showed a wide range of apparent amylose content from 3.0 to 28.1%. This diverse range in amylose content might offer choices for breeders to select cultivars with appropriate amylose content in breeding program. The data from rapid visco analyzer (RVA) analysis and genotyping with SNPs marker of SSIIa confirmed the different rice cultivars were of three groups, S-type, M-type and L-type by confirming functional SSIIa present or absent, although zymogram assay did not clearly indicate SSIIa enzyme activity in these cultivars except Ta Soke Pwa and MR219-9 had indicated this enzyme activity. This information is useful in enhancing the development of new rice cultivars with desirable quality characteristics in Asian rice cultivars.